Tofu Liquid Waste Treatment Using Effective Volume of Anaerobic Sequencing Batch Reactor (ASBR) - Budiastuti, Herawati; Rachmawati, Anissa Nurul; Agustin, Delliana; Paramitha, Tifa; Rusdianasari (KOVALEN: Jurnal Riset Kimia, 2024)
The tofu industry produces liquid waste containing high organic compounds. Organic compounds in liquid waste can threaten aquatic ecosystems if discharged directly into water bodies. One of the most effective wastewater treatment systems is the treatment using Anaerobic Sequencing Batch Reactor (ASBR). Besides being able to reduce the content of organic compounds, ASBR can produce biogas, and its decomposing microorganisms do not flow into the effluent stream. The purpose of this study was to evaluate the performance of ASBR at an effective reactor volume according to the design. This is because the use of ASBR in previous studies had not reached the operational stage and did not use an effective volume reactor. The stages of waste treatment using ASBR include the seeding, acclimatization, and operation stages. Waste treatment took place at room temperature in the reactor with an effective volume of 6 L. The operating parameters tested were MLVSS, COD, BOD, pH, and cumulative biogas volume. The results obtained show that the seeding process took 56 days, acclimatization took 10 days, and the operation lasted for 17 days. The efficiency of reducing COD concentration was 60%, the efficiency of reducing BOD concentration was 35.65%, and the cumulative volume of biogas produced was 24,120 mL at the operating stage. The use of the ASBR system at an effective volume of 6 L resulted in the successful processing of tofu liquid waste.